Penerapan Teori Perilaku Informasi Menurut Kulthau di Perpustakaan - Leila Setia Ningsih; Nazmiah Yusdi Arwana; Febrian Elly Sakinah Sari,; Juwita Syahrina; Franindya Purwaningtyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information seeking behavior refers to patterns of human behavior related to the nature of information, both in terms of using and seeking information. The term